The EVA Study: Early Vascular Aging in Women With History of Preeclampsia - Werlang, Ana; Paquin, Amélie; Coutinho, Thais (Journal of the American Heart Association, 2023)
Background Early vascular aging (EVA) is associated with higher risk of adverse cardiovascular events and can be estimated noninvasively by assessing arterial hemodynamics. Women with a history of preeclampsia have increased risk of cardiovascular disease, but underlying mechanisms are incompletely understood. We hypothesized that women with a history of preeclampsia display persistent arterial abnormalities and EVA in the postpartum period. Methods and Results We performed a comprehensive, noninvasive arterial hemodynamic evaluation in women with a history of preeclampsia (n=40) and age-matched controls with previous normotensive pregnancies (n=40). We used validated methods integrating applanation tonometry with transthoracic echocardiography to obtain measures of aortic stiffness, steady and pulsatile arterial load, central blood pressure, and arterial wave reflections. Presence of EVA was defined as aortic stiffness higher than that predicted from reference values based on the participant's age and blood pressure. The association of preeclampsia with arterial hemodynamic variables was assessed with multivariable linear regression, and the association of severe preeclampsia with EVA was assessed with multivariable logistic regression, adjusted for confounders. We found that women with a history of preeclampsia had greater aortic stiffness, steady arterial load, central blood pressure, and arterial wave reflections when compared with controls. We observed a dose-response relationship, with the greatest abnormalities observed in subgroups with severe, preterm, or recurrent preeclampsia. Women with severe preeclampsia had 9.23 times greater odds of having EVA as compared with controls (95% CI, 1.67-51.06, =0.011) and 7.87 greater odds of EVA as compared with women with nonsevere preeclampsia (95% CI, 1.29-47.77, =0.025). Conclusions Our study comprehensively characterizes arterial hemodynamic abnormalities after preeclampsia and suggests that specific subgroups of women with a history of preeclampsia exhibit greater alterations in arterial hemodynamics related to arterial health. Our findings have important implications for understanding potential links between preeclampsia and cardiovascular events, and suggest women with severe, preterm, or recurrent preeclampsia as subgroups who may deserve intensification of efforts for prevention and early detection of cardiovascular disease.